2016
DOI: 10.1186/s13048-016-0251-x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging for distinguishing ovarian clear cell carcinoma from high-grade serous carcinoma

Abstract: BackgroundTo compare the magnetic resonance imaging (MRI) features of ovarian clear cell carcinoma (CCC) and high-grade serous carcinoma (HGSC), to distinguish CCC from HGSC.MethodsMRI features (laterality, shape, size, configuration, papillary projection, signal intensity, enhancement, peritoneal implant, lymphadenopathy, ascites) of 40 tumors in 37 patients with CCC, confirmed by surgery and pathology, were compared with those of 62 tumors in 40 patients with HGSC. Statistical analysis was performed using Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…The possible reason may be that Type II cancer comprised of only one pathological subtype, while there were four subtypes identified in Type I OEC patients resulting in much heterogeneity in the lesion. Also, previous research found that hyperintense cystic components were often detected on T1WI in clear cell and endometroid ovarian cancer than in other subtypes [29, 30]. These findings are supported by our study.…”
Section: Discussionsupporting
confidence: 92%
“…The possible reason may be that Type II cancer comprised of only one pathological subtype, while there were four subtypes identified in Type I OEC patients resulting in much heterogeneity in the lesion. Also, previous research found that hyperintense cystic components were often detected on T1WI in clear cell and endometroid ovarian cancer than in other subtypes [29, 30]. These findings are supported by our study.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in line with those of previous studies (17). In addition, a previous study demonstrated that ADC value is helpful for differentiating ovarian endometrioid adenocarcinoma from high-grade serous adenocarcinoma (25). As the pathological subtypes were relatively small, further investigation focused on discriminating different types of BOTs and MOTs using ADC values is warranted.…”
Section: Discussionsupporting
confidence: 91%
“…In the clinic, functional magnetic resonance imaging (MRI) is a preferred choice for diagnosis and evaluation of OC [ 37 ], and both ascites, as well as laterality, can be recognized as features from an MRI image. Ma et al compared the features of ovarian clear cell carcinoma and high-grade serous carcinoma, which included ascites and laterality [ 38 ]. Despite the authors emphasizing the consistency of MRI and intraoperative examinations, no performance evaluation data such as accuracy was provided.…”
Section: Discussionmentioning
confidence: 99%